(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
In this article, the views on the development and upbringing of the individual in Uzbek folk pedagogy, the harmony of the active position of the individual in society and social relations, the role of different activities in the development of the child’s personality, development, upbringing and formation are interrelated.